Udział biegłego w procesie do dyspensy od małżeństwa zawartego a niedopełnionego - Kamiński, Rafał (Ius Matrimoniale, 2017)
The article concerns the role of an expert in a special matrimonial process, which is an administrative procedure for a dispensation from a marriage ratum et non consummatum. Analyzing the current legislation, the author characterizes the originality of the process and reflects on the necessity of appearing an expert to provide a „physical argument” for non-consummation of a marriage. In the following, the specific tasks of the expert and the evidential value of his opinion were characterized.